Role of microsphere as drug carrier for osteogenic differentiation. Issue 5 (24th March 2021) - Jun, Yuju; Oh, Hyunyoung; Karpoormath, Rajshekhar; Jha, Amitabh; Patel, Rajkumar
Abstract: Drug delivery system in sustainable manner has a great potential in biomedical applications. Along with its biocompatibility, microspheres ability to encapsulate and promote sustained release of drugs or growth factor makes them an ideal carrier for the transport of bioactive molecules for tissue regeneration and controlled drug delivery applications. Additionally, the injectable form of small spherical microsphere facilitates the accurate drug delivery. These drug carrier microspheres have significant role in osteogenic differentiation. The invasive delivery of bioactive molecules promotes bone regeneration. The drug stimulates the osteogenic differentiation of stem cell and promotes the damaged tissue for self-repair. This review elaborates the role of polymeric microspheres and the composite microspheres as a drug carrier for osteogenic differentiation. Graphical Abstract: